Intrathoracic pressure swings induced by simulated obstructive sleep apnoea promote arrhythmias in paroxysmal atrial fibrillation - Schlatzer, C; Schwarz, E; Sievi, N; Clarenbach, C; Gaisl, T; Haegeli, L; Duru, F; Stradling, J; Kohler, M (Oxford University Press, 2015)
AIMS: There is preliminary evidence for a link between obstructive sleep apnoea (OSA) and arrhythmias such as paroxysmal atrial fibrillation (PAF) and sudden cardiac death but underlying mechanisms remain largely unknown. METHODS AND RESULTS: In this interventional crossover study, we evaluated whether intrathoracic pressure changes, induced by simulated OSA, trigger premature cardiac beats, and alter measures of ventricular repolarization [QTc and Tpeak-to-Tend (TpTec) intervals] in patients with PAF. 12-Lead-electrocardiograms were recorded continuously in 44 patients, while simulating obstructive apnoea (Mueller manoeuvre, MM), obstructive hypopnoea (inspiration through a threshold load, ITH), end-expiratory central apnoea (AP), and during normal breathing (NB) in randomized order. The prevalence of OSA in these 44 patients was assessed by a sleep study. Atrial premature beats (APBs) occurred more frequently during MM (55% of patients) and ITH (32%), but not during AP (14%), compared with NB (9%) (P < 0.001, P = 0.006 and P = 0.688, respectively). Mueller manoeuvre led to a significant prolongation of QTc and TpTec intervals (+17.3 ms, P < 0.001 and +4.3 ms, P = 0.005). Inspiration through a threshold load significantly increased QTc (+9.6 ms, P < 0.001) but not TpTec. End-expiratory central apnoea did not alter QTc and TpTec intervals. According to the sleep study, 56% of patients had OSA (apnoea hypopnoea index ≥5). CONCLUSION: Simulated OSA induces APBs which may be important in patients with PAF, because the majority of episodes of PAF has been shown to be triggered by APBs. Simulated OSA leads to a significant prolongation of ventricular repolarization.